Relação pedagógica professor-estudante concepções docentes - Caroline Damásio Bueno; Nilce Maria da Silva Campos Costa (UniEVANGÉLICA, 2018)
Objective: To know the teacher perspective on the pedagogical relationship with the students and to identify the main manifestations in the relational domain. Methods: This is a descriptive and exploratory study of a qualitative approach, with twelve nutrition teachers. Data collection was carried out by menas of one-on-one interviews and application of a semistructured script. Categories were identified after content analysis. Results: It was observed that 58% of the teachers evaluated the relationship as successful and 42% unsuccessful. Positive attitudes were considered: dialogue, participation, responsability and recognition; and negatives were: passivity, resistance to new pedagogical approaches and disinterest. Conclusions: The evaluation of the relationship based on the attitudes of some teachers and their students refers to the presence or absence indicador, because corroborated with the pedagogical discourses ofthe university, of wich, there is a forecast of appropriation of certain knowledge, development of essential faculties for professional training.